Design and fabrication of hydro fruit picker / Muhammad Ammar Hamizan Zolkeplee and Abdul Hadi Abdul Rahim @ Ibrahim - Zolkeplee, Muhammad Ammar Hamizan; Abdul Rahim @ Ibrahim, Abdul Hadi (School of Mechanical Engineering, 2023)
Fabrication and design of a hydro fruit picker is a project that improvises a standard fruit picker in order to achieve the goal of a multi-function picker. At the same time, the purpose of this picker is to ensure that fruits can be plucked in a safer manner than standard pickers. The issue that the former has is finding a type of picker that is ideal for commercial tasks. Designing the model, drilling, cutting, and joining are some of the approaches that are employed in this product manufacture. The literature review helped improve the project and design and sketching to ensure project completion. Fabrication and testing the product is the last and the main important step in order to complete the project. The goal of this product is to create a fully functional hydro fruit picker. The increase of commercial farms from time to time is the main objective of why this project chose to design and fabricate this type of picker that will improve the function of traditional fruit pickers